There is power in a union? Union members' preferences and the conditional effect of labour unions on left parties in different welfare state programmes - Fabian Engler; Linda Voigt (British Journal of Industrial Relations, 2022)
This article studies the effect of labour unions on policy-making in six different parts of the welfare state (passive and active labour market policy, employment protection, old-age pensions, health care and education) in OECD countries after 1980 with a two-level strategy: At the micro-level, we investigate union members' preferences. Ordered logit regression analyses indicate that union members favour generous social policies more strongly than non-members. Moreover, this effect is stronger for programmes closely related to the labour market than for programmes without a strong labour market link. At the macro-level, we investigate the conditional effect of unions on left parties expecting the former to push the left towards more generous labour market-related (but not towards less-labour market-related) programmes. Regression analyses essentially provide evidence for such a relationship. Overall, unions have been powerful in promoting their members' social policy preferences via left parties in government but their power is recently vanishing.
Keywords: 330